Critical metals handbook - Gunn, Gus, 1951- (John Wiley & Sons, 2014)
"The proposed book will provide a unique, one-stop source of information on diverse aspects of the critical metals, including geology, deposits, processing, applications, environmental issues and markets"--Provided by publisher.